1983
DOI: 10.3133/cir886
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the world distribution of metal-rich subsea manganese nodules

Abstract: CONTENTS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Interest in mining these deposits developed fol lowing a series of papers by Mero (1959Mero ( ,1965 who called attention to the feasibility of their commercial recovery. McKelvey and others (1983) suggested that molybdenum, vanadium, and several of the rare earth elements might also be recoverable as by-products of possible future ex tractions of nickel, copper, and cobalt. These elements, as well as titanium, zinc, barium, lead, strontium, and yttrium, are present in the nodules in the range of < 0.01 to nearly 0.1 percent (McKelvey and others, 1983).…”
Section: By David Z Piper and Theresa R Swint-iki Us Geological mentioning
confidence: 99%
See 1 more Smart Citation
“…Interest in mining these deposits developed fol lowing a series of papers by Mero (1959Mero ( ,1965 who called attention to the feasibility of their commercial recovery. McKelvey and others (1983) suggested that molybdenum, vanadium, and several of the rare earth elements might also be recoverable as by-products of possible future ex tractions of nickel, copper, and cobalt. These elements, as well as titanium, zinc, barium, lead, strontium, and yttrium, are present in the nodules in the range of < 0.01 to nearly 0.1 percent (McKelvey and others, 1983).…”
Section: By David Z Piper and Theresa R Swint-iki Us Geological mentioning
confidence: 99%
“…McKelvey and others (1983) suggested that molybdenum, vanadium, and several of the rare earth elements might also be recoverable as by-products of possible future ex tractions of nickel, copper, and cobalt. These elements, as well as titanium, zinc, barium, lead, strontium, and yttrium, are present in the nodules in the range of < 0.01 to nearly 0.1 percent (McKelvey and others, 1983). Mero (1965) outlined the features of the geographic distribution of nodules in the Pacific Ocean and the re gional variations in their composition.…”
Section: By David Z Piper and Theresa R Swint-iki Us Geological mentioning
confidence: 99%
“…Raw geochemical data were taken directly from McKelvey (1983) who, in turn, retrieved them from the Scripps Institute of Oceanography (SIO) Nodule Data Base (Frazer and Fisk, 1980). Data were prepared by forward transformation of coordinates from geographic to Cartesian coordinates in the Hatano equal area projection (Evenden, 1990).…”
Section: Purposementioning
confidence: 99%
“…Deep sea manganese nodules are recognized as a potential resource of nickel, copper, manganese and, to a lesser extent, cobalt. Few studies have been oriented toward detailed specification of the nature and distribution of nodule geochemistry on a global basis (McKelvey, 1983;Lenoble, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Manganese balances for the oceans indicate that the nodule material is derived to a small extent from exogen ous sources (influx from the continents and from submarine weathering) and to a larger extent from endogenous ones (volcanism and exhalations), where it is assumed that considerable accumulation has occurred in pre-Pleistocene beds, with a maxi mum of nodule formation in the Eocene period [9,12,16]. The economic significance of the nodules is determined primarily by combined contents of manganese, nickel, cobalt, and copper oxides in excess of 35%, the sum of nickel and copper at least 1.1% and cobalt above 0.5%, or the sum of copper, nickel and cobalt 2% for the same manganese con tent [10,13].…”
mentioning
confidence: 99%